Approaching The Language of Umayyad Amatory (Ghazal) From The Daily Life Language And Its Drawing Near To The Prose Language - جبارة, زينب مديح (lark, 2019)
AbstractThis research is regarded a part of an extensive study of amatory ( ghazal) language at the Umayyad era. It is found that one of the evolution characteristics in language of Umayyad amatory (ghazal) is its approach to the language of daily life and its tendency towards the prose language. Therefore, the language of Arabic poetry, which is characterized by its powerful eloquence, cohesion, coherence and valuable, is changed. The researcher is here used poetic examples (or paradigms) which are related to the poets of town and desert alike. So, it has been manifested, via the uses of women, in these two regions, the language of daily life, when the poet narrates the talk of his women companions. The poet is also tended to transfer the text prose language away of its poetic tendencies via his using of parentheses sentences. It should also be noted that the grammatical error has infiltrated to the language of Umayyad poets, and this is exampled throughout documented paradigms of the poetry of Omar Ibn Abi Rabia and Jamil Buthainh. Thus, this is led to the approach of poetic text from the daily life language, and its trend towards the prose language.
Keywords: Umayyad; daily life language; Amatory; Omar Ibn Abi Rabia; Jamil Buthainh; prose language; Poetic text